CONSUMER ACCEPTANCE AND ECONOMIC VALUE OF Cratoxylum formosum ESSENTIAL OIL - Muhamad Yusup Hidayat; Ridwan Fauzi; Grace Serepina Saragih; Alfonsus H. Harianja (Indonesian Journal of Forestry Research, 2023)
Cratoxylum formosum (Jack) Benth. & Hook.f. ex Dyer is one of the plant species that have the potential to be developed into an antibacterial and antioxidant essential oil product. This study was conducted to determine the value of organoleptic tests and the consumers' willingness to pay (WTP) for the three variants of Cratoxylum formosum essential oil products. For the parameters of colour, hedonic test values and score tests showed good results; panellists did not mind the pure and mixed Cratoxylum formosum essential oil colours. However, for fragrance parameters, the hedonic test showed a dislike score. Most panellists disliked the strong "scent of leaves" of pure C. formosum oil. The score test showed satisfactory values, the panellists accept the fragrance of Cratoxylum formosum essential oil, but it is necessary to add a more preferred scent mixture to reduce the strong original fragrance of the oil. The cost of production of Cratoxylum essential oil is Rp.7,259.23 (USD 0.48)/mL or Rp.72,592.30 (USD 4.84) for every 10 mL. Based on the cost ofproduction, the appropriate selling value for every 10 mL of Cratoxylum essential oil is a minimum of USD 4.84.